Estudio de la calidad de energía eléctrica en la Corporación Ecuatoriana de Aluminio Cedal S.A. ubicada en la ciudad de Latacunga en el año 2021. - Antamba Valenzuela, Bryan Fernando (2021)
The present study was carried out at Corporación Ecuatoriana de Aluminio CEDAL S.A., an industry located in the city of Latacunga and dedicated to the manufacture and commercialization of aluminum extrusions at national and international level. The intention of this project is to analyze the power quality in the power supply system in the extrusion area of the plant, through national and international standards such as CONELEC 005/18, ARCERNNR 200/20 and IEEE std 519, IEEE std 1159. This study includes a bibliographic and field review, which provided significant knowledge for the development of the proposed topic. Data on electrical parameters in the three transformers present in the extrusion area were recorded with a FLUKE 435- SII network analyzer, in addition to this, the load survey and updating of single-line diagrams of the electrical system were elaborated, which were subsequently used in the simulations performed in the EASY POWER program through which the most significant disturbances of the system such as low power factor and voltage and current harmonics could be analyzed. These problems are relevant in the economy of an industry because they cause damage to machinery, electrical elements, and an excessive payment in energy consumption. Harmonic mitigation methods have been proposed based on the analysis of the data obtained through the analyzer and simulations, showing the feasibility and benefits of the project, both economic and technical.